Information and Communications Technology in Engineering Graphics and Design Classrooms: A post COVID-19 era - Mlambo, Philani Brian (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
The integration of information and communications technology in teaching and learning is growing at an exponential rate due to many factors we have observed lately, such as the outbreak of COVID-19. The unprecedented outbreak of COVID-19 took the world by surprise. Many sectors such as health and education were left shattered due to the outbreak of COVID-19. The outbreak compelled the educational sector to come up with alternative majors to keep the teaching and learning process alive as the physical classes were suspended as means to curb the spread of COVID-19. In an attempt to investigate different ways Engineering Graphics and Design teachers used to conduct lessons during the COVID-19 lockdown, this study employed a qualitative approach. Data was collected through semi-structured interviews and analysed using thematic analysis. The findings of this study indicate that COVID-19 did influence the way teachers are teaching post-COVID-19. The study findings further reveal that WhatsApp was the tool most teachers relied on to keep teaching and learning alive, however, some teachers were experiencing problems. The study recommends that teachers should continue using WhatsApp as a way of extending lessons during home hours.